Verifying the validity of creatinine measurement in low‐concentrated urine spot samples—Photospectrometry versus liquid chromatography–tandem mass spectrometry. Issue 6 (28th January 2021) - Franz, Simon; Skopp, Gisela; Dame, Torsten; Musshoff, Frank
Abstract: One of the major challenges of testing drugs of abuse is the detection of highly diluted urine samples. The ingestion of a large amount of fluid can considerably reduce the concentration of substances, possibly resulting in inaccurate drug testing. For detection, determination of urinary creatinine is a widely established procedure. In this study, results from the most popular methods, including photospectrometry (Jaffe) and liquid chromatography–tandem mass spectrometry (LC–MS/MS), have been compared regarding 327 urine abstinence control samples. Because samples with creatinine concentrations close to the cutoff of 20 mg/dL are of particular interest, only samples below 50 mg/dL were considered. Results revealed a close correlation of creatinine concentrations by both analytical methods with an R 2 value of 0.9005. A mean concentration difference of 3.30 ± 3.45 mg/dL was observed, indicating a moderate underestimation by the Jaffe reaction. Graphical analyses showed high accordance between both methods with only a few outliers. Due to easy handling and for economic reasons, the spectrometric method is often preferred over LC–MS/MS. For urine samples with creatinine concentrations close to the cutoff, confirmation through a second method should be performed to avoid a possible disadvantage or even severe consequences for the respective individual. It is recommended that each laboratory establishes a reliable verification method. Abstract : Photospectrometry (Jaffe) and LC–MS/MS for determination of creatinine in low‐concentrated urine samples is compared. Confirmation through a second method for samples with creatinine concentrations below the cutoff is recommended to avoid a possible disadvantage for participants of drug‐testing programs.